A familial case of Birt–Hogg–Dubé syndrome complicated with lung cancer: a case report and literature review - Feng, Jingjing; Yu, Yunxia; Liu, Yi; Ding, Yi; Mu, Junyi; Jiang, Rong; Sharma, Lokesh; Jie, Zhijun (Frontiers in Medicine, 2025)
The Birt–Hogg–Dubé (BHD) syndrome is a rare, autosomal dominant disorder caused by germline mutations in the FLCN gene, which encodes a tumor suppressor protein. The syndrome is characterized by cutaneous fibrofolliculomas, pulmonary cysts, spontaneous pneumothoraces, and renal tumors. We report a rare familial case of BHD complicated by primary lung adenocarcinoma in a 69-year-old man. The patient presented with a persistent cough, bilateral pulmonary cysts, and a 4 × 3 cm tumor in the left lung lobe. Genetic testing revealed a novel pathogenic FLCN mutation (c.295_311del p.Asp99Ter) in the patient and several family members, including his son and brother, both of whom exhibited pulmonary cysts and histories of pneumothoraces. The patient was diagnosed with invasive lung adenocarcinoma. Although tumor progression was stabilized with treatment, the clinical course was complicated by severe hyperthyroidism, liver injury, and myelosuppression. This case highlights the complexities of managing lung cancer in BHD patients and suggests a potential role for FLCN mutations in tumorigenesis. Our findings underscore the importance of early diagnosis, genetic testing, and a multidisciplinary approach to the management of BHD in order to improve patient outcomes and prevent complications. In addition, we conducted a literature review of previously reported FLCN mutations in BHD syndrome.